Pathology and Molecular Epidemiology of Fowl Adenovirus Serotype 4 Outbreaks in Broiler Chicken in Abu Dhabi Emirate, UAE - Hassan Zackaria Ali Ishag (Veterinary Sciences, 2022)
Background: Fowl adenovirus serotype 4 (FAdV-4), causing inclusion body hepatitis (IBH) and hydropericardium hepatitis syndrome (HPS), is responsible for the significant economic losses in poultry industry worldwide. This study describes FAdV disease and molecular characteristics of the virus as the first report in UAE. Methodology: Clinical, necropsy, histopathology, qPCR and phylogenetic analysis of hexon gene were used to diagnose and characterize the virus. Results: The age of the infected broiler chicken was 2–4 weeks. The morbidity and mortality rates ranged between 50 and 100% and 44 and 100%, respectively. Clinically, sudden onset, diarrhea, anemia and general weakness were recorded. At necropsy, acute necrotic hepatitis, with swollen, yellowish discoloration, enlarged and friable liver; hydropericarditis with hydropericardium effusions; and enlarged mottled spleen were observed. Histopathology examination revealed degeneration and necrosis, lymphocytic infiltration and inclusion bodies. The qPCR analysis detected the virus in all samples tested. Hexon gene sequence analysis identified FAdV serotype 4, species C as the major cause of FAdV infections in UAE in 2020, and this strain was closely related to FAdV-4 circulating in Saudi Arabia, Pakistan, Nepal and China. Conclusion: The serotype 4, species C, was the common FAdV strain causing IBH and HPS episodes in the region. This result may help design effective vaccination programs that rely on field serotypes.